Analisis Kualitas Pelayanan Air Minum Pada Perusahaan Daerah Air Minum (Pdam) Tirtanadi Cabang Tuasan - Ika Suhaila; Abdul Kadir; Armansyah Matondang (Universitas Medan Area, 2022)
The quality of service is the priority of PDAM Tirtanadi Tuasan Branch to customers. This research aims to analyze the quality of drinking water services provided by PDAM Tirtanadi Tuasan Branch along with i ts supporting factors and inhibition. The theory used is from Zeithaml and Bitner which is the benchmark of quality judging by several indicators of reliability, responsiveness, assurance, empathy, and tangible. The research method used is a qualitative approach by means of observation, interview and documentation. The results of this study show that the quality of drinking water service provided by PDAM Tirtanadi Tuasan Branch is not fully effective. This can be said to have not been effective on the basis of some indicators that were used as a benchmark of research has not been carried out optimally. Supporting factors and inhibition are also determinants of the quality of service provided.